2012
DOI: 10.1111/j.1741-3737.2012.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude Toward Voluntary Childlessness in Europe: Cultural and Institutional Explanations

Abstract: The Attitude Toward Voluntary Childlessness in Europe: Cultural and Institutional ExplanationsThe prevalence and social acceptance of childlessness have increased in recent decades. Still, little is known about how this social acceptance is shaped, the extent to which approval of childlessness differs across Europe, and what factors cause potential cross-national variation. The authors used data from the European Social Survey 2006 ( N = 36,187) to examine the attitude toward voluntary childlessness in 20 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 46 publications
7
92
1
7
Order By: Relevance
“…This normative pressure was widespread in CEE countries until recently (see, e.g., Merz and Liefbroer 2012;Sobotka 2016), but it also helps to explain the low childlessness levels observed among some religious and ethnic minorities in countries where childlessness is otherwise relatively common and accepted. The broad acceptance and prevalence of voluntary childlessness is closely linked with low religiosity (e.g., Abma and Martinez 2006;Tanturri and Mencarini 2008;Burkimsher and Zeman, Chap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This normative pressure was widespread in CEE countries until recently (see, e.g., Merz and Liefbroer 2012;Sobotka 2016), but it also helps to explain the low childlessness levels observed among some religious and ethnic minorities in countries where childlessness is otherwise relatively common and accepted. The broad acceptance and prevalence of voluntary childlessness is closely linked with low religiosity (e.g., Abma and Martinez 2006;Tanturri and Mencarini 2008;Burkimsher and Zeman, Chap.…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis of European survey data, Merz and Liefbroer (2012) found that approval of voluntary childlessness was closely related to the progression of the second demographic transition, with respondents in Norway, Denmark, and the Netherlands expressing the most positive views on voluntary childlessness.…”
Section: Introductionmentioning
confidence: 99%
“…As more couples delay childbearing, the issue of declining reproductive capacity with age becomes increasingly important. In addition, as more young adult women spend extended periods in education or pursuing career opportunities that have recently opened up to women, they may repeatedly decide to postpone childbearing, and thus drift into childlessness (Merz and Liefbroer 2012). Such individuals, who express a positive fertility intention but postpone childbearing until it is "too late", are described by Berrington (2004) as "perpetual postponers".…”
Section: A Continuum Of Childlessnessmentioning
confidence: 99%
“…They also benefited from expanding educational opportunities, including a gradual rise in university education. In the Western world, people born between the mid-1950s and 1970 continued the sociocultural changes initiated by the older cohorts, which resulted in a widening acceptance of less conventional family forms and living arrangements, including voluntary childlessness (Sobotka and Testa 2008;Merz and Liefbroer 2012;Kreyenfeld and Konietzka 2017). These changes also involved increasing gender equality, especially in the domestic sphere (McDonald 2000).…”
Section: Social Economic and Cultural Factor Trends Affecting Cohormentioning
confidence: 99%
“…In addition, the negative attitudes towards childlessness (Sobotka and Testa 2008;Merz and Liefbroer 2012) explain why fertility decline was largely driven by falling second-birth rates, especially in cohorts bearing children during the state-socialist era (Sobotka 2011). The same factors should also operate in Eastern Europe.…”
Section: Social Economic and Cultural Factor Trends Affecting Cohormentioning
confidence: 99%